Can we correct first metatarsal rotation and sesamoid position with the 3D Lapidus procedure?. Issue 3 (April 2022) - Ferreyra, M.; Viladot Pericé, R.; Nuñez-Samper, M.; Ibáñez, L.; Ibarra, M.; Vilá-Rico, J.
Highlights: There are few studies that study the correction of radiological parameters with the Lapidus 3D technique. Radiographic outcomes of triplanar correction using the 3D Lapidus procedure are excellent. The Lapidus 3D technique allows the position of the sesamoids to be corrected. Abstract: Objective: We examine the technique and radiographic outcomes obtained with triplanar first tarsometatarsal arthrodesis (3D Lapidus) for the surgical correction of hallux valgus (HV). This procedure, apart from correcting angular deformity 1st–2nd intermetatarsal angle, HV angle, etc., is specifically intended to act on first ray pronation and place the sesamoids in their normal position, to alleviate the metatarsalgia often occurring in HV before and after surgery, possibly caused by their abnormal position. This study aims to examine the radiographic outcomes of the 3D Lapidus procedure. Materials and methods: Retrospective study of 37 feet operated on from April 2019 to December 2019, with a minimum 1-year follow-up (mean 420 days), using the 3D Lapidus procedure. Radiographic outcomes were evaluated. Results: The intermetatarsal angle decreased from a mean value of 16.42° to 5.62° (p < 0.0001). The HV angle decreased from a mean value of 32.12° to 8.05° (p < 0.0001). The preoperative first metatarsocuneiform angle, with a mean value of 21.86°, was null after arthrodesis (p < 0.0001). The tibial sesamoid position, according to the Hardy and Clapham classification, decreased from a mean value of 4.84 to 1.27 after surgery, within normality (p < 0.0001). Discussion: Correction of the deformity in a single plane is generally insufficient. It is necessary to act on the three planes of space to correct the deformity, obtain good outcomes, and avoid recurrence. Conclusions: Radiographic outcomes of triplanar correction with the 3D Lapidus procedure are excellent, achieving statistically significant differences in all parameters studied.